High Q diamond hemispherical resonators: fabrication and energy loss mechanisms. (14th July 2015) - Bernstein, Jonathan J; Bancu, Mirela G; Bauer, Joseph M; Cook, Eugene H; Kumar, Parshant; Newton, Eric; Nyinjee, Tenzin; Perlin, Gayatri E; Ricker, Joseph A; Teynor, William A; Weinberg, Marc S
Abstract: We have fabricated polycrystalline diamond hemispheres by hot-filament CVD (HFCVD) in spherical cavities wet-etched into a high temperature glass substrate CTE matched to silicon. Hemispherical resonators 1.4 mm in diameter have a Q of up to 143 000 in the fundamental wineglass mode, for a ringdown time of 2.4 s. Without trimming, resonators have the two degenerate wineglass modes frequency matched as close as 2 Hz, or 0.013% of the resonant frequency (~16 kHz). Laser trimming was used to match resonant modes on hemispheres to 0.3 Hz. Experimental and FEA energy loss studies on cantilevers and hemispheres examine various energy loss mechanisms, showing that surface related losses are dominant. Diamond cantilevers with a Q of 400 000 and a ringdown time of 15.4 s were measured, showing the potential of polycrystalline diamond films for high Q resonators. These resonators show great promise for use as hemispherical resonant gyroscopes (HRGs) on a chip.